Newly established forests dominated global carbon sequestration change induced by land cover conversions - Dailiang Peng; Bing Zhang; Shijun Zheng; Weimin Ju; Jing M. Chen; Philippe Ciais; Huadong Guo; Yuhao Pan; Le Yu; Yidi Xu; Bin Zhao; Jón Atli Benediktsson; et al. (Nature Communications)
Abstract Land cover conversions (LCC) have substantially reshaped terrestrial carbon dynamics, yet their net impact on carbon sequestration remains uncertain. Here, we use the remote sensing-driven BEPS model and high-resolution HILDA+ data to quantify LCC-induced changes in net ecosystem productivity (NEP) from 1981 to 2019. Despite global forest loss and cropland/urban expansion, LCC led to a net carbon gain of 229 Tg C. Afforestation and reforestation increased NEP by 1559 Tg C, largely offsetting deforestation-driven losses (−1544 Tg C), with newly established forests in the Northern Hemisphere driving gains that counterbalanced emissions from tropical deforestation. Regional carbon gains were concentrated in East Asia, North America, and Europe, while losses occurred mainly in the Amazon and Southeast Asia. Although smaller in area, newly established forests exhibited higher sequestration efficiency than degraded older forests, emphasizing the role of forest age in shaping global carbon sink dynamics. These findings highlight the critical importance of afforestation, forest management, and spatially informed land-use strategies in strengthening carbon sinks and supporting global carbon neutrality goals.